2020
DOI: 10.15243/jdmlm.2021.082.2689
|View full text |Cite
|
Sign up to set email alerts
|

Land-use changes and slope positions impact on the degradation of soil functions in nutrient stock within the Kalikungkuk micro watershed, East Java, Indonesia

Abstract: Degradation of soil functions in storing and cycling nutrients may be related to topography and land-use change. The research aimed to analyze the impact of land-use changes and slope positions on soil function in nutrient stock within Kalikungkuk micro watershed of East Java, Indonesia. Four different land-uses such as vegetable crops, agroforestry, shrub and forest were selected with three slope positions (e.g. ridge, slope, and valley), and three replications of each. Soil samples were collected at 0-10, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
1
0
2
Order By: Relevance
“…The exchangeable K content at both 0-20 cm and 21-40 cm depth was significantly affected by land use, slope, and their interaction with p < 0.05 (Table 5). Fitria et al (2021) also reported that land use systems and slope positions affected soil exchangeable K content within 0-100 cm soil depth. The exchangeable K content on 8-15% slopes is significantly higher than on 16-40% slopes.…”
Section: Nutrient Content In the Soilmentioning
confidence: 92%
“…The exchangeable K content at both 0-20 cm and 21-40 cm depth was significantly affected by land use, slope, and their interaction with p < 0.05 (Table 5). Fitria et al (2021) also reported that land use systems and slope positions affected soil exchangeable K content within 0-100 cm soil depth. The exchangeable K content on 8-15% slopes is significantly higher than on 16-40% slopes.…”
Section: Nutrient Content In the Soilmentioning
confidence: 92%
“…Praktik pemupukan termasuk dalam pengelolaan hara memengaruhi tingkat kesburan dan ketersediaan hara. Penggunaan pupuk anorganik dan organik seperti penambahan pupuk kendang sapi mampu meningkatkan efisiensi P sebesar 57% (Eckhardt et al, 2018) Penambahan pupuk kandang (kotoran ayam) dan pupuk anorganik (SP-36) di lahan ladang berdampak pada konsentrasi P tersedia yang lebih besar (meningkat 75-175 %) dibandingkan dengan P tersedia di lahan hutan pada berbagai kedalaman tanah (Fitria et al, 2021).…”
Section: Pendahuluanunclassified
“…Pengelolaan dan masukan input seperti penggunaan pupuk anorganik dan organik menjadi penyebab tidak berbeda nyatanya status kesuburan tanah. Hal ini selaras dengan penelitian yang dilakukan oleh (Fitria, et al, 2021) saat membandingkan pengaruh posisi lereng terhadap penggunaan lahan hutan, agroforestri, dan dengan pertanian intensif.…”
Section: Pengaruh Tingkat Kelerengan Terhadap Tingkat Kesuburan Tanahunclassified
“…The evenness of the bacteria in the sample area was not different; this was demonstrated by the Simpson index value, which was relatively the same (Table 2). (Fitria and Kurniawan, 2021), and utilizing machines for crop management could modify the soil physicochemical properties, consequently altered the diversity of bacteria in the studied area. This finding was corresponding with another study conducted by Bissett et al (2011) and Suleiman et al (2013).…”
Section: Soil Bacteria Diversitymentioning
confidence: 99%